Diphenhydramine dependence through deep intramuscular injection resulting in myonecrosis and prolonged QT interval. (5th March 2014) - Chen, T.‐Y.; Yeh, Y.‐W.; Kuo, S.‐C.; Chen, C.‐Y.; Lin, T.‐P.; Chang, C.‐C.
Summary What is known and objective Diphenhydramine (DPH) is a first‐generation antihistamine, which is useful in treating allergic reaction, and is usually considered innocuous. We describe a retired nurse with history of depression, who began to develop drug‐seeking behaviour after her first receiving of an intramuscular (IM) DPH injection due to urticaria. Case summary The 49‐year‐old patient had developed IM DPH dependence within 4 months. She needed to receive psychiatric inpatient treatment because of depressive mood, serious myonecrosis over injected sites, and prolongation of QT interval. What is new and conclusion This is the first reported case of DPH dependence through the IM route. Second‐generation antihistamines might be better choices for patients with psychiatric illness by reason of their lower effects on central nervous system and lower risk of abuse.